2019
DOI: 10.1177/0309364618798173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unloader knee braces on medial meniscal strain

Abstract: Two unloader knee braces effectively reduced strain in the medial meniscus with an intact anterior cruciate ligament during dynamic activities. Neither brace made a significant reduction in strain for anterior cruciate ligament-deficient knees. Clinical relevance Unloader knee braces could be used to reduce the medial meniscus strain following meniscal surgery and during rehabilitation in patients with an isolated medial meniscus injury. However, these braces cannot be recommended for this purpose in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, during pilot testing, we investigated the potential of applying the method presented here to the posterior meniscus roots. Although other studies have demonstrated the applicability of sensors at the posterior periphery of menisci, 18,19,45 we were unable to attach the displacement sensors without interference of the surrounding soft tissues. Sta ¨rke et al [46][47][48] used a different method, which allowed a direct force measurement at the posterior meniscus roots.…”
Section: Forces Acting On the Anterior Meniscus Attachmentsmentioning
confidence: 81%
“…However, during pilot testing, we investigated the potential of applying the method presented here to the posterior meniscus roots. Although other studies have demonstrated the applicability of sensors at the posterior periphery of menisci, 18,19,45 we were unable to attach the displacement sensors without interference of the surrounding soft tissues. Sta ¨rke et al [46][47][48] used a different method, which allowed a direct force measurement at the posterior meniscus roots.…”
Section: Forces Acting On the Anterior Meniscus Attachmentsmentioning
confidence: 81%
“…Prophylactic bracing has demonstrated reduced strain on the posterior horn of the medial meniscus in cadaveric models and has been studied in several populations with widely variable results. 91 In vivo, a medial unloader brace has demonstrated increased peak knee flexion moment and increased knee stability when performing single-leg squat, forward lunge and during ambulation. 30 In collegiate football players, prophylactic bracing compared with no brace significantly reduced medial collateral ligament (MCL) and meniscus injuries.…”
Section: Bracingmentioning
confidence: 99%
“…With overall low quality studies and widely variable data, it is unclear whether bracing can prevent meniscus injury in athletes or occupational groups with high risk physical demands. Prophylactic bracing has demonstrated reduced strain on the posterior horn of the medial meniscus in cadaveric models and has been studied in several populations with widely variable results 91. In vivo, a medial unloader brace has demonstrated increased peak knee flexion moment and increased knee stability when performing single-leg squat, forward lunge and during ambulation 30.…”
Section: Preventionmentioning
confidence: 99%